Aberrant Right Subclavian Artery in a Dog - Clinical and Imaging Aspects - Antunes, Helloine Mariane Ribeiro; Vieira, Nathany Camila; Franco, Ellen Ronara de Jesus; Sousa, Valéria Régia Franco; Néspoli, Pedro Eduardo Brandini; Almeida, Arleana do Bom Parto Ferreira de (Acta Scientiae Veterinariae, 2022)
Background: Aberrant right subclavian artery is only rarely observed in veterinary medicine. Some animals may present postprandial regurgitation and progressive weight loss, which is considered an incidental finding unrelated to clinical alterations. Advanced imaging techniques such as thoracic CT scan, magnetic resonance imaging (MRI) and contrast angiography are used for the accurate detection of lesions, anatomical changes and specific information about vascular rings. This paper describes the clinical changes, imaging exams and therapeutic approach in a female dog with megaesophagus induced by an aberrant right subclavian artery. Case: A 2-month-old female bull terrier, weighing 1.6 kg, with a history of regurgitation immediately or a few minutes after a meal, diarrhea, polyphagia, progressive emaciation and apathy for 45 days, was treated at a University Veterinary Hospital. The dog’s physical examination revealed 7% dehydration and body condition score 1 (scale 1 to 5), but no cardiac or pulmonary alterations upon auscultation. The hematological analysis and renal and hepatic serum enzymes were within the normal range for the species. In view of the presumptive clinical diagnosis of vascular anomaly, suggested by the contrast X-ray examination, a chest tomography was performed, which revealed altered aortic arch shape and contours, and a posterior aneurysm in the area of ​​abnormal connection of the right subclavian artery. The patient was released with a prescription for conservative dietary management for megaesophagus. Within two weeks, the patient returned with a report of a good response to the prescribed therapy, absence of vomiting and diarrhea, and an increase in body weight. Surgical correction was recommended, but has not been performed so far, but conservative treatment for megaesophagus was continued. No further episodes of regurgitation were identified during the nine-month follow-up period. Discussion: In the case reported here, the right subclavian artery is considered anatomically atypical because it arises directly from the aortic arch. This vascular anomaly passes on to the right pectoral limb, dorsal to the esophagus, contracting it in its dorsal aspect. It tends to affect purebred dogs, occurring more frequently in Irish setters, German shepherds and Labrador retrievers, although it has been described in other breeds such as the bull terrier documented here and mixed breed dogs. Vascular ring anomalies may not cause clinical changes in animals and represent only incidental findings, or they may lead to gastrointestinal changes resulting from esophageal stricture, contributing to megaesophagus and clinical signs of esophageal obstruction, especially in recently weaned puppies. Such alterations were observed in this case, with the dog presenting regurgitation, immediately or a few minutes after a meal, megaesophagus, diarrhea and progressive weight loss. A CT scan was performed to confirm the type and location of the vascular anomaly and diagnostic accuracy, as recommended in the literature. Dietary therapy is one of the approaches adopted for patients presenting with regurgitation resulting from megaesophagus secondary to vascular anomalies. The dog in this report responded well to the medical therapy; nevertheless, the treatment of choice to correct the esophageal obstruction caused by this anomaly is surgical sectioning of the aberrant vessel by right intercostal thoracotomy, given that the degree of esophageal dilation and dysfunction tends to increase over time. However, at this time, the animal’s owner decided to suspend the recommended surgical procedure. Keywords: aberrant right subclavian artery, female dog, megaesophagus. Título: Artéria Subclávia Direita Aberrante em cão - aspectos clínicos e de imagem. Descritores: artéria subclávia direita aberrante, cão fêmea, megaesôfago.